Using technology to enhance special education - Bakken, Jeffrey P.; Obiakor, Festus E. (Advances in special education, 2023)
Using Technology to Enhance Special Education, Volume 37 of Advances in Special Education, is a logically, thoughtfully organized, and well-sequenced text. It focuses on how general and special educators can use technology to work with children and youth with disabilities. This cutting-edge book involves researchers, scholars, educators, and leaders who are knowledge producers in the field. It is written to respond to today's changing world where technology has become a very powerful force. As it stands, the world is getting smaller and smaller; and what is happening in a location quickly becomes known everywhere. For example, during the tense periods of the global COVID pandemic, technology became the livewire of our world. This book begins with an introduction to technology and students with disabilities; and the remaining chapters focus on the role of technology in the education of students with learning disabilities, emotional and/or behavioral disorders, and intellectual disabilities, autism spectrum disorders, physical and health impairments, hearing impairments/deafness, visual impairments, and traumatic brain injuries. In addition, some chapters focus on the role of technology in achieving equitable and inclusive education, building culturally and linguistically responsive general and special education, and creatively using digital comics to improve written narratives. In the end, this book concludes with a chapter that forward looking ways to infuse technology in special education. We feel that this volume is an excellent resource for special education researchers, scholars, practitioners, and professionals who teach and serve students with disabilities.